Hubungan Tebal Lemak Bawah Kulit dengan Tingkat Kebugaran Jasmani pada Siswa Sekolah Dasar di Daerah Rural Kota Padang - Intan Nurwida Hayati Yasrial; Cimi Ilmiawati; Lili Irawati; Afriwardi Afriwardi (Fakultas Kedokteran, Universitas Andalas, 2021)
Background: Physical fitness is important for school-age children to improve their learning and playing abilities. Physical fitness is greatly influenced by environmental factors and body adiposity. Previous studies have shown that children in rural areas have higher level of physical fitness and lower skinfold thickness than children in urban areas. Objective: To determine the correlation of skinfold thickness and level of physical fitness in school-age children in rural area, Padang city. Methods: This study was an analityc observational study with cross – sectional design and involving 52 subjects. This research was conducted at SDN 13 Sungai Pisang, Padang City on Juni – November 2020. The independent variable was the skinfold thickness using skinfold caliper on the triceps and the dependent variable was the level of physical fitness assessed by the Indonesian Physical Fitness Level. Data were analyzed using the Pearson correlation test. Results: The median value of skinfold thickness was 2 mm. Most subjects (42.4%) had low level of physical fitness levels. There was no statically significant correlation between skinfold thickness and physical fitness (Pearson’s r=0.124; p= 0.380). Conclusion: There is no relationship between the skinfold thickness with the level of physical fitness